Process Diagnosis prior to the application of Lean Manufacturing - Juárez López, Yolanda; Pérez Rojas, Aurora; Rojas Ramírez, Jorge (Nexo Revista Científica, 2012)
In implementing a solution guide for manufacturing problems such as an unsatisfied demand, a previous diagnosis is necessary. In this paper we describe how this was developed for the case of railroad material enterprises at the Mexican State of Hidalgo. The phases considered are: the description of the system under study, the capture and assess of the system performance, the definition of the observed problems, and its association with the causes generating them. As the performance evaluating criteria the Lean Production paradigm, originated in Japan, has been selected, due to its adequacy to the case because of its focus in process waste reduction and participative problem solving. For this case, the wastes to cope with are the long set-up times, the high rate of bad products, and the lack of adequate equipment maintenance. DOI: http://dx.doi.org/10.5377/nexo.v25i1.792 Nexo Revista Científica,Vol. 25, No. 01, pp.09-17/Junio 2012